Effects of postural specific sensorimotor training in patients with chronic low back pain: study protocol for randomised controlled trial. Issue 1 (December 2015) - McCaskey, Michael; Schuster-Amft, Corina; Wirth, Brigitte; de Bruin, Eling
Abstract Background Sensorimotor training (SMT) is popularly applied as a preventive or rehabilitative exercise method in various sports and rehabilitation settings. Yet, there is only low-quality evidence on its effect on pain and function. This randomised controlled trial will investigate the effects of a theory-based SMT in rehabilitation of chronic (>3 months) non-specific low back pain (CNLBP) patients. Methods/Design A pilot study with a parallel, single-blinded, randomised controlled design. Twenty adult patients referred to the clinic for CNLBP treatment will be included, randomised, and allocated to one of two groups. Each group will receive 9 x 30 minutes of standard physiotherapy (PT) treatment. The experimental group will receive an added 15 minutes of SMT. For SMT, proprioceptive postural exercises are performed on a labile platform with adjustable oscillation to provoke training effects on different entry levels. The active comparator group will perform 15 minutes of added sub-effective low-intensity endurance training. Outcomes are assessed on 4 time-points by a treatment blinded tester: eligibility assessment at baseline (BL) 2–4 days prior to intervention, pre-intervention assessment (T0), post-intervention assessment (T1), and at 4 weeks follow-up (FU). At BL, an additional healthy control group (n  = 20) will be assessed to allow cross-sectional comparison with symptom-free participants. The main outcomes are self-reported pain (Visual Analogue Scale) and functional status (Oswestry Disability Index). For secondary analysis, postural control variables after an externally perturbed stance on a labile platform are analysed using a video-based marker tracking system and a pressure plate (sagittal joint-angle variability and centre of pressure confidence ellipse). Proprioception is measured as relative cervical joint repositioning error during a head-rotation task. Effect sizes and mixed-model MANOVA (2 groups × 4 measurements for 5 dependent variables) will be calculated. Discussion This is the first attempt to systematically investigate effects of a theory-based sensorimotor training in patients with CNLBP. It will provide analysis of several postural segments during a dynamic task for quantitative analysis of quality and change of the task performance in relation to changes in pain and functional status. Trial registration Trial registry number on cliniclatrials.gov isNCT02304120, first registered on 17 November 2014.